Different interpretation of additional evidence for HTA by the commissioned HTA body and the commissioning decision maker in Germany: Whenever IQWiG and Federal Joint Committee disagree - C. M. Dintsios; F. Worm; Jörg Ruof; M. Herpers (Health Economics Review, 2019)
Background: The purpose of this study was to analyse the impact of commissioned addenda by the Federal Joint Committee (FJC) to the HTA body (IQWiG) and their agreement with FJC decisions and to identify potential additional decisive factors of FJC. Methods: All available relevant documents up to end of 2017 were screened and essential content extracted. Next to descriptive statistics, differences between IQWiG and FJC were tested and explored by agreement statistics (Cohen's kappa and Fleiss' kappa) and ordinal logistic regression. Results: Most of the 90 addenda concerned oncological products. In all contingent comparisons, positive changes in added benefit or evidence level on a subpopulation basis (n = 124) prevailed negative ones. Fleiss' ordinal kappa for agreement of assessments, addenda, and appraisals reached a moderate strength for added benefit (0.474, 95%-CI, 0.408-0.540). Overall agreement between addenda and appraisals on a binary nominal basis is poor for added benefit (Cohen's kappa 0.183; 95%-CI: 0.010-0.357) ranging from 'less than by chance' (respiratory diseases) to 'perfect' (neurological diseases). The OR of the selected regression model showed that i) mortality, ii) unmet need, the positions of iii) the physicians' drug commission and iv) medical societies, and v) the annual therapeutic costs of the appropriate comparative therapy had a high influence on FJC's appraisals deviating from IQWiG's addenda recommendation. Conclusions: IQWiG's addenda have a high impact on decision-maker's appraisals offering additional analyses of supplementary evidence submitted by the manufacturers. Nevertheless, the agreement between addenda and appraisals varies, highlighting different decisive factors between IQWiG and FJC.
Keywords: I18; 330; Addenda; AMNOG; IQWiG; Federal Joint Committee; Early benefit assessment; (added benefit; Evidence quality; Agreement statistics)